Synthesis, Characterization and Biological Studies on Coordination Polymers of Co(II), Ni(II), Cu(II), Mn(II) and Zn(II) with Bis-Bidentate Schiff Base - Patil, R.M.; R. Chaurasiya, Shivkumar (Asian Journal of Chemistry, 2010)
Co(II), Ni(II), Cu(II), Mn(II) and Zn(II) polychelates with N,N'-bis-[2-hydroxy-napthalidine]-4,4'-diaminodiphenylmethane [H2-NalDADPM], have been synthesized and characterized by elemental analysis, magnetic susceptibility, spectral techniques like UV-Visible, IR, NMR, Mass, ESR and thermal studies. The molar conductivity data indicates that the chelates are non-electrolytes. Analytical data supports 1:1 (M:L) stoichiometry. The electronic spectra along with the magnetic data suggest octahedral geometry for all the chelates. The IR data shows the ligand H2-NalDADPM function as bis-bidentate ligand coordinating through ON-NO donor system. The ligand and its polychelates have also been screened for their antimicrobial activity using various microorganisms and all of them have been found to be moderately active against them.